Nauczanie cudzoziemców polskiego języka specjalistycznego (ze szczególnym uwzględnieniem języka ekonomicznego i języka biznesu) - Jarosz, Wiesława (Neofilolog, 2010)
The notion of specialist language is described for the purposes of this article, followed by a short history of the teaching techniques used since the 1970s, where students have typically been taught general Polish as well as specialist language. The materials and techniques used for the fields of business and economics are given as examples and described in detail.